Analis Perilaku Konsumen Masyarakat Ponorogo Sesaat dan Sesudah Datangnya Bulan Ramadhan - Anis Faridatul Hasanah (Civiliza Publishing, 2020)
Abstract. This study aims to determine how the consumer behavior of the Ponorogo community during and after Ramadan. This study uses a descriptive qualitative research analysis approach. The data collection is obtained from several techniques, including secondary data, interviews with informants, and observation techniques through documentation of some data or image archives related to the object of research. From this study it is known that 95% of respondents stated that they experienced an increase in consumption costs during the month of Ramadan. The increase in consumption costs can be seen through the increase in food and drink consumption expenditures and the purchase of clothing for the preparation of Eid. Consumer behavior in the month of Ramadan with other months experiences a significant difference. This can be proven by the increasing number of people shopping at the D-2 market ahead of Ramadan to prepare for consumption in that month and H-10 before Eid to buy clothes, sandals or shoes and prepare for Eid preparation.